INCREASING OF STUDENTS LEARNING OUTCOMES THROUGH APPLYING THE MODEL OF LEARNING STUDENT ACHIEVEMENT DIVISION TEAMS (STAD) - Wistiana Supriyadi (Pedagogi, 2016)
The objective of this study is to describe the Student Teams Achivement Division (STAD) to improve the learning outcomes of students in learning science. The subjects consisted of 40 student of fourth grader of SDN Subangjaya 2. The method wich used in this study is a classroom action research, that has a four steps (planning, implementation, observation, and reflection. This study was carried out by three cycles. The instruments wich used ware the observation sheet and learning outcomes questions. The result in this study ware gained the average of study result in the first test the average students score is 61,5 or 37,5%. After the act of learning has the outcomes learning of students score. In the first cycle obtained an average grade of 68 or 60 %, the second cycle was obtained an average grade of  72,25 or 77,5 %, and the third cycle is obtained an average grade of 100%. The suggest that the implementation of a model of learning model STAD can improve student learning outcomes.Keywords: model STAD, learning outcomes